Analysis of Differences in Business Etiquette between China and Africa: The Case of Senegal and Morocco - Kemo Badiane,; Huiting Lin,; Hsin-I Lee, (Journal of Educational Issues, 2024)
After China’s reform and opening-up, trade exchanges between China and Africa have risen sharply. Africa, a continent rich in natural resources, attracts Chinese businessmen and companies. Furthermore, many African countries strongly encourage Chinese firms to invest in. This paper aims at studying the differences in business practices between China and Africa through document analysis, interviews with experienced local businessmen. Focusing on China and two African countries (Senegal & Morocco), our findings show that the acceptance and respect of cultural differences play a key role in the capacity of Chinese companies and their African counterparts to successfully start business in both countries. Theoretical contribution, managerial implications and limitations are also discussed.